Novel design of phase demodulation scheme for fiber optic interferometric sensors in the advanced undergraduate laboratory. (1st November 2022) - Zhang, Gang; Ge, Qiang; Wang, Huisheng; Xuqiang, Wu; Yu, Benli
Abstract: Phase modulation depth (PMD) is crucial for the phase demodulation scheme of fiber optic interferometric sensors. The novel design of phase generated carrier differential-cross-multiplying (PGC-DCM) demodulation schemes allows undergraduates to understand the operation principle of the sensors and explore the connection between the PMD and the system performance. The system mainly consists of a laser, a fiber Michelson interferometer (FMI), a data acquisition card and a host computer. The simulation signal is first applied on the sensing arm of the FMI by a piezoelectric transducer and induces the phase difference shift between the two arms. Next the signal-to-noise ratios (SNRs) of the demodulated signals from the PGC-DCM algorithms under different PMD values are tested and an optimum PMD value is found. Thus, a proportion integral differential (PID) module is designed and integrated with the demodulation algorithm to calibrate the PMD to the optimum value. An ellipse fitting algorithm (EFA) is used to estimate the real-time PMD of the system that is then fed into the PID module. The amplitude of the laser modulation signal is controlled by the PID module, which is proportional to the PMD. Moreover, the response linearity, dynamic range, total harmonic distortion and phase resolution of the system are investigated.